Injectable hyaluronic acid/poly(ethylene glycol) hydrogels crosslinked via strain-promoted azide-alkyne cycloaddition click reaction. (1st August 2017) - Fu, Shuangli; Dong, Hui; Deng, Xueyi; Zhuo, Renxi; Zhong, Zhenlin
Graphical abstract: Highlights: Hyaluronic acid is modified by attaching cyclooctyne moieties on the carboxyl groups. Quadruply azide-terminated poly(ethylene glycol) is prepared as a crosslinking agent. Crosslinked HA-PEG hydrogels are formed at physiological conditions. The hydrogels are strong, slowly biodegradable, and biocompatible. Abstract: This paper reports injectable hyaluronic acid (HA)-based hydrogels crosslinked with azide-modified poly(ethylene glycol) (PEG) via the strain-promoted azide–alkyne cycloaddition (SPAAC) between cyclooctyne and azide groups. Cyclooctyne-modified HA (Cyclooctyne-HA) is prepared by the reaction of HA with 2-(aminoethoxy)cyclooctyne. To crosslink the modified HA, quadruply azide-terminated poly(ethylene glycol) (Azide-PEG) is designed and prepared. The mixture of Cyclooctyne-HA and Azide-PEG gelates in a few minutes to form a strong HA-PEG hydrogel. The hydrogel has fast gelation time, good strength, and slow degradation rate, because of the high reactivity of SPAAC, high crosslinking density originated from the quadruply-substituted Azide-PEG, and the good stability of the crosslinking amide bonds. In vitro cell culturing within the hydrogel demonstrated an excellent cell-compatibility. The bioorthogonality of SPAAC makes the hydrogel injectable. With good mechanical properties and biocompatibility, the hydrogel would be useful in a wide range of applications such as injection filling materials for plastic surgery.